2020
DOI: 10.1158/2159-8290.cd-19-1262
|View full text |Cite
|
Sign up to set email alerts
|

The INPP4B Tumor Suppressor Modulates EGFR Trafficking and Promotes Triple-Negative Breast Cancer

Abstract: Inactivation of the tumor suppressor lipid phosphatase INPP4B is common in triplenegative breast cancer (TNBC). We generated a genetically engineered TNBC mouse model defi cient in INPP4B. We found a dose-dependent increase in tumor incidence in INPP4B homozygous and heterozygous knockout mice compared with wild-type (WT), supporting a role for INPP4B as a tumor suppressor in TNBC. Tumors derived from INPP4B knockout mice are enriched for AKT and MEK gene signatures. Consequently, mice with INPP4B defi ciency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 87 publications
(108 reference statements)
1
38
0
Order By: Relevance
“…Inactivation of the lipid phosphatase INPP4B is frequently observed in triple-negative breast cancer, where it functions as a tumor suppressor by regulating RTK trafficking and degradation. As a consequence, loss of INPP4B prolongs both PI3K and ERK activation [ 42 ]. In addition, recent findings suggest that INPP4B facilitates PI3KCA crosstalk with Wnt signaling in ER+ breast cancer via PI(3,4)P2-to-PI(3)P conversion on late endosomes, suggesting that these tumors may be targeted with combined PI3K and Wnt/β-catenin therapies [ 43 ].…”
Section: Genetic Alterations Of the Pi3k Pathway In Breast Cancer And Clinical Implicationsmentioning
confidence: 99%
“…Inactivation of the lipid phosphatase INPP4B is frequently observed in triple-negative breast cancer, where it functions as a tumor suppressor by regulating RTK trafficking and degradation. As a consequence, loss of INPP4B prolongs both PI3K and ERK activation [ 42 ]. In addition, recent findings suggest that INPP4B facilitates PI3KCA crosstalk with Wnt signaling in ER+ breast cancer via PI(3,4)P2-to-PI(3)P conversion on late endosomes, suggesting that these tumors may be targeted with combined PI3K and Wnt/β-catenin therapies [ 43 ].…”
Section: Genetic Alterations Of the Pi3k Pathway In Breast Cancer And Clinical Implicationsmentioning
confidence: 99%
“…In general, our observations caution against the use of a binary PIK3CA -mutant-centric approach to predict PI3K pathway activity outcomes. Moreover, we note that numerous alternative genetic changes – including PIK3CA amplification, loss of PTEN or INPP4B – may converge on increased, and perhaps dose-dependent, PI3K pathway activation [3,30,32,44]. Importantly, such PIK3CA mutant-independent pathway activation is captured by the transcriptional footprint-based PI3K activity scores used in our study and will thus contribute to the values observed in non- PIK3CA mutant tumours.…”
Section: Discussionmentioning
confidence: 70%
“…The apparent biphasic relationship between single versus multiple copies of PIK3CA mutation and stemness scores warrants further study, but is likely to reflect poorly understood regulatory aspects of intracellular signalling networks. We therefore caution against the use of a PIK3CA-mutant-centric approach to predict PI3K pathway activity, given that numerous alternative genetic changes -including PIK3CA amplification, PTEN and INPP4B loss -may converge on increased PI3K pathway activation [3,26,33,34]. These will be captured by the PI3K activity signature used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In TNBC tumors, inactivating mutations mutations, loss of PTEN, or heterozygous deletion of INPP4B are the more frequently observed PI3K pathway-related genetic alterations (Cancer Genome Atlas Network, 2012). Mice bearing TNBC tumors engineered with an INPP4B deficiency showed increased sensitivity to PI3K inhibition (Liu et al, 2020).…”
Section: Phosphoinositide 3-kinase Signaling Pathway and Its Aberrant Activation In Breast Cancermentioning
confidence: 99%